A case report of a successfully treated patient of granulomatosis with polyangitis and diabetes mellitus - Mahin, Tasnova; Haque, Ariful; Samad, Tabassum; Rahim, Muahmmad Abdur; Ul Haque, Wasim Md Mohosin (BIRDEM Medical Journal, 2022)
Granulomatosis with polyangitis (previously known as Wegener’s granulomatosis) is an antineutrophilcytoplasmic antibody (ANCA) associated vasculitis (AAV). Its main characteristics are necrotizing granulomatous inflammation and paucimmune vasculitis in small and medium sized vessels. Here, we present a case history of a 42-year-old diabetic patient, who presented with cough, epistaxis, deafness and acute kidney injury. Though ANCAs were negative, imaging and histopathological features were consistent with the diagnosis of granulomatosis with polyangitis. With supportive management of diabetes and renal failure, the patient was given immunosuppressive therapy with 4 cycles of intravenous methylprednisolone and cyclophosphamide resulting in improvement of renal function and respiratory symptoms.A high degree of suspicion is needed for diagnosis of granulomatosis with polyangitis as it is relatively rare and timely treatment may result in favourable outcome. BIRDEM Med J 2022; 12(2): 161-164